Motivations for promiscuous behaviour among some female students in institutions of higher learning in Zimbabwe - Mugodzwa, T.; Matope, Nogget; Maruzani, Nyevero; Mugodzwa, D.M. (Midlands State University, 2019)
This study investigated motivations for prostitution among female students in an institution of higher learning in Zimbabwe. The main purpose was to capture reasons why some female students engage in prostitution in the face of immense challenges of the risk of acquiring sexually transmitted diseases and the deadly HIV and AIDS virus. A prostitute in the traditional African culture and the current Zimbabwean society is not only viewed with a lot of suspicion, but is regarded as immoral and a social deviant and misfit, yet prostitution is dramatically on the increase in institutions of higher learning in Zimbabwe. This therefore calls for a thorough interrogation of the motives behind prostitution by female students. Using structured interviews and open and close ended questionnaires and focus group discussions, 180 female students and 30 male students were identified through purposeful, non random sampling process in an institution of higher learning. The study was taken in the period September 2009 to June 2010. The study found out that female students engage in prostitution because of poor family background, compounded by increased economic hardships currently being experienced by most Zimbabweans. Most of them said they were motivated to prostitution to raise money for fees, accommodation, typing of assignments and dissertations, and their general welfare. The first category of these University prostitutes comprises of those who are motivated by the daily demands of the stomach, because it is common knowledge that the stomach does not entertain appeals to reason and justice, but food. The main reason for prostitution therefore was poverty. The second category of prostitutes is made up of those who may be soundly funded by their guardians, but experience challenges in writing and passing assignments, dissertations and examinations. This sophisticated class of prostitutes thrives on luring lecturers and bright male students and exchange sex for good grades. The third category of female students who prostitute is for the sexual variety, pleasure and satiation. The study recommends that the Government funded assistance in the form of cadetship should be made more accessible to students in financial need. Institutions of higher learning should put in place programs that can empower students financially by offering vacation placements and engage in income generating projects on a large scale spearheaded by students. On the other hand, parents and guardians should ensure that they provide adequate money for those they are responsible for. The institutions of higher learning could also go a long way by ensuring that adequate on-campus accommodation is provided for their student population.